Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:;4.4
Step-by-step explanation: Since it varies inversely we know G times H squared is equal to some constant, k. So we have G*H*H=k. We are told that when H=4, G=.25. Plugging this in, we have .25*4*4=k. This simplifies to 4=k. Our new equation is G*H*H=4. Now, we want to solve for G when H=.3. We plug it in. G*.3*.3=4 => G*.09=4. G=4/.09. This means G is approximately 44.4.
Answer:
G = 44.44
Step-by-step explanation:
Given the mathematical expression and data;
[tex] G = \frac {1}{H^{2}} [/tex]
H = 4 and G = 0.25
First of all, we would determine the constant of proportionality, k.
[tex] G = \frac {k}{H^{2}} [/tex]
Making k the subject of formula, we have;
k = GH²
Substituting the values, we have;
k = 0.25 * 4²
k = 0.25 * 16
k = 4
Next, we find the value of G when H = 0.3;
[tex] G = \frac {k}{H^{2}} [/tex]
[tex] G = \frac {4}{0.3^{2}} [/tex]
[tex] G = \frac {4}{0.09} [/tex]
G = 44.44
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.